1998
DOI: 10.1055/s-2007-1016276
|View full text |Cite
|
Sign up to set email alerts
|

Co-Culture Update: Creating an Embryotrophic Environment In Vitro

Abstract: As infertility treatments evolve and techniques are developed to improve the fertilization and pregnancy rates, it is clear that the in vitro environment in which the gametes/embryos are cultured is less than perfect when compared to the in vivo counterpart. This becomes a serious problem for couples who seek to have children but are limited by unsuccessful attempts to become pregnant and a technology that is behind in mimicking the in vivo environment that would enhance gamete interaction and embryo developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In porcine EC, the use of oviductal epithelial cells has shown a beneficial effect on final monospermy results after IVF Romar et al 2001) and the cells have been used with good results in bovine EC systems (Katska et al 1995(Katska et al , 1998. In the same way, in an attempt to mimic in vivo conditions, coculture of embryos and endometrial cells has been performed in humans (Katsuragawa et al 1995;Conway-Myers 1998) and in mice (Lai et al 1996;Soong et al 1998) and has been shown to improve embryonic development. In pigs, fertilization takes place in the oviduct and the embryo enters the uterus at the 2-to 4-cell stage (Harper 1988 ; Fig.…”
Section: Embryo Culturementioning
confidence: 99%
“…In porcine EC, the use of oviductal epithelial cells has shown a beneficial effect on final monospermy results after IVF Romar et al 2001) and the cells have been used with good results in bovine EC systems (Katska et al 1995(Katska et al , 1998. In the same way, in an attempt to mimic in vivo conditions, coculture of embryos and endometrial cells has been performed in humans (Katsuragawa et al 1995;Conway-Myers 1998) and in mice (Lai et al 1996;Soong et al 1998) and has been shown to improve embryonic development. In pigs, fertilization takes place in the oviduct and the embryo enters the uterus at the 2-to 4-cell stage (Harper 1988 ; Fig.…”
Section: Embryo Culturementioning
confidence: 99%
“…Same beneficial effects of the co-culture have been obtained with embryos cultured in groups rather than alone (Spindler & Wildt, 2002). It is likely that the secretion and the sharing of beneficial paracrine factors and embryotrophic compounds modulate the nutrient profile and protect cell against culture-induced stress, ROS and toxins Conway-Myers, 1998;Plachot, 1996;Wiemer, Cohen, Tucker, & Godke, 1998).…”
Section: Again the Balance Between Reactive Oxygen Species (Ros) Andmentioning
confidence: 99%
“…Same beneficial effects of the co‐culture have been obtained with embryos cultured in groups rather than alone (Spindler & Wildt, ). It is likely that the secretion and the sharing of beneficial paracrine factors and embryotrophic compounds modulate the nutrient profile and protect cell against culture‐induced stress, ROS and toxins (Buccione, Vanderhyden, Caron, & Eppig, ; Conway‐Myers, ; Plachot, ; Vanderhyden, Caron, Buccione, & Eppig, ; Wiemer, Cohen, Tucker, & Godke, ). In general, the presence of denuded oocytes in co‐culture positively influence the cumulus cells activities of mammalian COCs due to an active exchange of oocyte‐secreted factors (OSFs) that regulate the oocyte metabolism, proliferation, cumulus expansion and differentiation (Gilchrist, Lane, & Thompson, ; Hussein, Thompson, & Gilchrist, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to wound repair, an area where coculture models have led to major advances is embryotrophic coculturing [28]. These models have reconstructed uterine tissue in vitro by using primary and immortalized cell lines and conditional media to host embryonic development [29].…”
Section: Benefits and Limitations Of Epithelial Cell Coculturementioning
confidence: 99%